Case report: A rare case of Rosai–Dorfman–Destombes disease after the COVID-19 infection - Gogia, Pooja; Tanni, Fahmina; Coca-Guzman, Juan; Chen, Neil; Huang, Yiwu (Frontiers in Medicine, 2022)
Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is known to cause immune dysregulation and, therefore, has varied and often rare presentations. Rosai–Dorfman–Destombes disease (RDD) is an unusual non-Langerhans cell (non-LC) histiocytosis presenting with massive lymphadenopathy and various systemic symptoms. A 55-year-old Asian-American woman with no significant medical history or recent use of new drugs initially presented with cervical lymphadenopathy and urticarial rash 1 week after receiving the COVID-19 messenger RNA (mRNA) vaccine (Moderna, mRNA-1273) against SARS-CoV-2. The biopsy of the skin rash was consistent with a drug reaction. Approximately 2 months later, she developed mild flu-like symptoms and was diagnosed with a COVID-19 infection. Her symptoms were mild and self-resolving. Approximately 3 months later, she developed a generalized patchy erythematous rash on the face and the body that gradually worsened; diffuse lymphadenopathy involving the bilateral cervical, axillary, and inguinal areas; and constitutional symptoms. Laboratory results were consistent with lymphopenia, anemia, and an elevated sedimentation rate. Supraclavicular lymph node biopsy showed Rosai–Dorfman disease with a marked polyclonal plasmacytosis. She was started on a tapering dose of corticosteroids and showed clinical improvements over the next few weeks. Herein, we present a rare case of a histiocytic disorder that developed after contracting the SARS-COV2 infection in the event of receiving a recent mRNA COVID vaccination.